Cine gastric MRI reveals altered Gut–Brain Axis in Functional Dyspepsia: gastric motility is linked with brainstem‐cortical fMRI connectivity - Sclocco, Roberta; Fisher, Harrison; Staley, Rowan; Han, Kyungsun; Mendez, April; Bolender, Andrew; Coll‐Font, Jaume; Kettner, Norman W.; Nguyen, Christopher; Kuo, Braden; Napadow, Vitaly (Neurogastroenterology and motility, 2022)
Background Functional dyspepsia (FD) is a disorder of gut–brain interaction, and its putative pathophysiology involves dysregulation of gastric motility and central processing of gastric afference. The vagus nerve modulates gastric peristalsis and carries afferent sensory information to brainstem nuclei, specifically the nucleus tractus solitarii (NTS). Here, we combine MRI assessment of gastric kinematics with measures of NTS functional connectivity to the brain in patients with FD and healthy controls (HC), in order to elucidate how gut–brain axis communication is associated with FD pathophysiology. Methods Functional dyspepsia and HC subjects experienced serial gastric MRI and brain fMRI following ingestion of a food‐based contrast meal. Gastric function indices estimated from 4D cine MRI data were compared between FD and HC groups using repeated measure ANOVA models, controlling for ingested volume. Brain connectivity of the NTS was contrasted between groups and associated with gastric function indices. Key Results Propagation velocity of antral peristalsis was significantly lower in FD compared to HC. The brain network defined by NTS connectivity loaded most strongly onto the Default Mode Network, and more strongly onto the Frontoparietal Network in FD. FD also demonstrated higher NTS connectivity to insula, anterior cingulate and prefrontal cortices, and pre‐supplementary motor area. NTS connectivity was linked to propagation velocity in HC, but not FD, whereas peristalsis frequency was linked with NTS connectivity in patients with FD. Conclusions & Inferences Our multi‐modal MRI approach revealed lower peristaltic propagation velocity linked to altered brainstem‐cortical functional connectivity in patients suffering from FD suggesting specific plasticity in gut–brain communication. Our multi‐modal MRI approach revealed lower peristaltic propagation velocity linked to altered brainstem‐cortical functional connectivity in patients suffering from FD suggesting specific plasticity in gut‐brain communication.